The beta‐cell in type 1 diabetes: What have we learned from proteomic studies?. Issue 7 (26th March 2015) - Crèvecoeur, Inne; Rondas, Dieter; Mathieu, Chantal; Overbergh, Lut; Cutler, Paul; Voshol, Hans
<x xml:space="preserve">Abstract</x> Pancreatic beta‐cells have a crucial role in the regulation of blood glucose homeostasis by the production and secretion of insulin. In type 1 diabetes (T1D), an autoimmune reaction against the beta‐cells together with the presence of inflammatory cytokines and ROS in the islets leads to beta‐cell dysfunction and death. This review gives an overview of proteomic studies that lead to better understanding of beta‐cell functioning in T1D. Protein profiling of isolated islets and beta‐cell lines in health and T1D contributed to the unraveling of pathways involved in cytokine‐induced cell death. In addition, by studying the serological proteome of T1D patients, new biomarkers and beta‐cell autoantigens were discovered, which may improve screening tests and follow‐up of T1D development. Interestingly, an important role for PTMs was demonstrated in the generation of beta‐cell autoantigens. To conclude, proteomic techniques are of indispensable value to improve the knowledge on beta‐cell function in T1D and the search toward therapeutic targets.